Effects of long-lasting massive dumping of dredged material on bottom sediment and water turbidity during port expansion works. (15th May 2022) - Palanques, Albert; Guillén, Jorge; Puig, Pere; Durán, Ruth
Abstract: The effects of massive dumping of dredged material were studied during and after the last large Barcelona port expansion. A benthic tripod equipped with a current meter, a turbidimeter and a video camera was deployed at the edge of the Barcelona shelf dumpsite. Additionally, sediment cores were taken before, during and after dumping at the tripod location. Previously, sediment samples were taken in the port expansion area. Dumping generated frequent (10–19 per day), high (>203.2 mg L −1 ) and short (50–90 min) suspended sediment concentration peaks along with shock waves that increased currents velocities. The dumped sediment formed a thin laminated deposit that accumulated beyond the limits of the dumpsite. This material was finer and had a lower trace metal content than the previous sediment at the dumpsite and the surface samples taken from the dredged area. Unconsolidated sediment left after dumping was available to be resuspended and advected, generating higher ambient suspended sediment concentrations (0.8–15.0 mg L −1 ) than before the dumping (0.4–2.0 mg L −1 ), which lasted several days. Results of this work suggest that after the end of a massive dumping in low dispersive environments, such as on the dumpsite of the Barcelona continental shelf, turbidity should continue to be monitored until the recovery of natural values. The characteristics of the bottom sediment should be periodically controlled beyond the limits of the dumpsite if the dumped material spilled outside its boundaries. Environmental guidelines for dredging activities should include specific actions for long-lasting massive dumping episodes regarding their spatial extent, considering the effects of the shock waves generated by dumping, and also the temporal evolution of the effects of dumping after its completion. Graphical abstract: Image 1 Highlights: The dumpsite water turbidity and seabed was affected during and after dumping. Dumping generated 502 suspended sediment peaks in 53 days. Dumping generated a thin laminated mud deposit extending outside the dumpsite limits. Mixing and dilution of dredged sediment decreased trace metals levels at the dumpsite. Guidelines should include actions for massive dumping in low dispersive environments.